KOMPATIBILITAS AJARAN ISLAM DENGAN HAM - Abdul Latief (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2012)
This research discussed the compatibility of Islamic teaching with Human Rights. The issue was how the suitablity between the Islamic Shar’i and Human Rights. In analyzing the problem, the author used Shar’i and anthropological approach to the deductive and inductive method. Basically this study was an elaboration of one of the central themes in Islamic Shar'i namely Human Rights, which currently marginalized from current Islamic thinking developing in society.